Mallacoota misool, a new species of Maeridae from West Papua (Crustacea: Peracarida: Amphipoda) - Hughes, Lauren E. (Zootaxa, 2016)
The new species Mallacoota misool is described from the West Macleur Gulf, West Papua. Mallacoota misool sp. nov. is exceptionally similar to the geographically close M. chandaniae Lowry & Springthorpe, 2005 known from the Gulf of Carpentaria in northern Australia and also reported from the South China Sea. Both species have a massive gnathopod 2 propodus defined by two large teeth. Mallacoota misool sp. nov. has the palm medial surface without a dense bunch of seta, which is present in M. chandaniae.